Understanding and Identifying Bullies in Al-Ishlahiyah Singosari Integrated Vocational School - Rahmafridaya, Salsa; Bilkist, Inacio Imelda Dewi; Fadhil, Rizqi; Simon, Irene Maya; Hasanah, Laili Uswatun; Pratiwi, Awalya Siska (Universitas Negeri Malang, 2024)
The widespread occurrence of bullying in schools today can have negative impacts and cause serious problems for the mental and academic well-being of both victims and perpetrators. This study aims to identify the perpetrators and victims of bullying at SMK Terpadu Al-Ishlahiyah Singosari and to strengthen programs for prevention and intervention. The research employs a descriptive quantitative method using the